2022
DOI: 10.3390/jcm11226705
|View full text |Cite
|
Sign up to set email alerts
|

More Space, Less Noise—New-generation Low-Field Magnetic Resonance Imaging Systems Can Improve Patient Comfort: A Prospective 0.55T–1.5T-Scanner Comparison

Abstract: Objectives: The objectives of this study were to assess patient comfort when imaged on a newly introduced 0.55T low-field magnetic resonance (MR) scanner system with a wider bore opening compared to a conventional 1.5T MR scanner system. Materials and Methods: In this prospective study, fifty patients (mean age: 66.2 ± 17.0 years, 22 females, 28 males) underwent subsequent magnetic resonance imaging (MRI) examinations with matched imaging protocols at 0.55T (MAGNETOM FreeMax, Siemens Healthineers; Erlangen, Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…Nevertheless, many patients comparing both MRI scanners did perceive the larger bore diameter positively, while only one patients rated the MRI examination with the low field MRI scanner as “slightly worse” compared to the standard MRI scanner. These findings are in line with the results presented by Rusche et al [20] Their study also came to the conclusion that patients perceive the increased amount of space during examinations with the low field MRI scanner positively.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, many patients comparing both MRI scanners did perceive the larger bore diameter positively, while only one patients rated the MRI examination with the low field MRI scanner as “slightly worse” compared to the standard MRI scanner. These findings are in line with the results presented by Rusche et al [20] Their study also came to the conclusion that patients perceive the increased amount of space during examinations with the low field MRI scanner positively.…”
Section: Discussionsupporting
confidence: 92%
“…The noise level during the scanning procedure has been reported to be a major factor influencing the subjectively perceived patient comfort during MRI examinations. [4,16,20] The findings of the present study confirm the objectively measured noise levels reported by Rusche et al They found that the low field MRI scanner produces significantly less noise compared to a standard MRI scanner with 1.5 T; regardless of the body region. [20] Despite a good mean rating for the standard MRI scanner in the present study (mean 3.72 ± 1.46, median 4 = "rather not unpleasant"), the low field MRI scanner was rated even better with a mean rating of 4.26 ± 1.22 (median 5 = "not unpleasant at all," P = .008// corrected P = .032).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations